Religiozne in etnične feministične manjšine v Turčiji - od marginalizacije do boja za feministično subjektiviteto - Frank, Ana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2011)
The aim of this article is to draw attention to the discrimination of minorities within feminism. In an analysis of the Turkish context, I claim that Islamic and Kurdish feminists are not accepted as legitimate feminist subjects in Turkish feminism. Applying the theory of intersectionality, which analyses intersections of discrimination, I claim that Muslim and Kurdish women suffer discrimination not only as women but also as members of the Kurdish ethnic minority and as believing and practising Muslims. The methodology is the analysis of primary sources of Turkish Muslim and Kurdish feminist activists, and a discursive deconstruction of hegemonic discourses of Kemalism, state feminism, Turkish and Kurdish nationalism, and patriarchal Islamism. I advocate the need to acknowledge the subjectivity of women in religious and ethnic feminist positions, since they fight for their rights and against hegemonic discourses in a feminist spirit. My critique focuses on nationalist and orientalist discourses of production of the Other and on feminisms that uncritically operate on behalf of colonial and state ideologies.
Keywords: feminism; feminizem; islam; manjšine; woman; ženske; Turčija; Turkey; Kurdi; subjektiviteta